Letter from San Luis Obispo Buddhist Church to Mrs. Chizuko Iwanaga - Ken Kitasako, Secretary of San Luis Obispo Buddhist Church::::::author::: (1957)
This letter from Ken Kitasako, Secretary of the San Luis Obispo Buddhist Church, to Mrs. Chizuko Iwanaga of Berkeley, California, states: "We have been informed that the obutsudan for our Buddhist Church here in San Luis Obispo is expected to arrive from Japan on the Kohko Maru on or about May 18th. As we understand it, this obutsudan comes disassembled packed in a box with all the accessories that go with it. This beautiful obutsudan is being sent from the Buddhist Home Church to our Church in San Luis Obispo. Whatever you can do to help expedite clearance at the Customs Office when it arrives will be greatly appreciated. Thank you very much. Very truly yours, SAN LUIS OBISPO BUDDHIST CHURCH By Ken Kitasako, Secretary. P.S.-My wife, Mutsuko, sends you her warmest regards."